Grandiose delusions: an experimental investigation of the delusion as defense. - Smith, N; Freeman, D; Kuipers, E (2005)
Two distinct roles for emotion in the development of delusions have been outlined. Some authors argue that delusions defend against low self-esteem and negative emotion (the delusion-as-defense account). Other authors hypothesize that delusions are not a defense but are a direct reflection of emotion and associated processes (the emotion-consistent account). An empirical investigation was conducted of the delusion-as-defense account with reference to grandiose delusions. Twenty individuals with grandiose delusions and 21 individuals without mental illness were compared on overt and covert measures of self-esteem. No evidence for a discrepancy between overt and covert self-esteem in individuals with grandiose delusions was found. One potential interpretation of the results is that the tasks were not able to penetrate defensive processes. However, we argue that in this group, the grandiose delusions do not currently defend against low self-esteem. Instead, grandiose delusions may in part be direct exaggerations of the emotional state of individuals.